2008
DOI: 10.1186/1471-2407-8-31
|View full text |Cite
|
Sign up to set email alerts
|

The impact of comorbidity and stage on ovarian cancer mortality: A nationwide Danish cohort study

Abstract: Background: The incidence of ovarian cancer increases sharply with age, and many elderly patients have coexisting diseases. If patients with comorbidities are diagnosed with advanced stages, this would explain the poor survival observed among ovarian cancer patients with severe comorbidity. Our aims were to examine the prevalence of comorbidity according to stage of cancer at diagnosis, to estimate the impact of comorbidity on survival, and to examine whether the impact of comorbidity on survival varies by sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 31 publications
7
86
0
Order By: Relevance
“…Our results are in agreement with studies that have identified greater risk of mortality in septic patients with higher number of comorbidities using a large US National Hospital Discharge Survey database from 1979 through 2003 [86]. Comorbidities as a predictor of mortality and hospital LOS had been reported in patients with cancer [87], patients with cirrhosis [88], critically ill patients in ICU [89], and general hospital population [90]. This association showed a possible synergy between the effects of sepsis and comorbidities, which suggest that treatment of comorbidities should be considered an integral part of clinical care for patients with sepsis.…”
Section: Cns Failuresupporting
confidence: 82%
“…Our results are in agreement with studies that have identified greater risk of mortality in septic patients with higher number of comorbidities using a large US National Hospital Discharge Survey database from 1979 through 2003 [86]. Comorbidities as a predictor of mortality and hospital LOS had been reported in patients with cancer [87], patients with cirrhosis [88], critically ill patients in ICU [89], and general hospital population [90]. This association showed a possible synergy between the effects of sepsis and comorbidities, which suggest that treatment of comorbidities should be considered an integral part of clinical care for patients with sepsis.…”
Section: Cns Failuresupporting
confidence: 82%
“…Treatment opportunities have changed since the CCI weights were constructed [22], and milder or more severe forms of some conditions might be assigned the same CCI weight. However data show a clear difference in survival between CCI scores 0 and 3, although the impact of comorbidity on mortality was smaller than what was shown from other Danish studies [6,7]. To further analyze whether differential health status could explain the survival differences, we adjusted for ASA score and secondly for BMI [12,40].…”
Section: Survivalmentioning
confidence: 61%
“…Cancer patients with lower socioeconomic positions also tend to have more comorbid conditions at time of diagnosis [5], a prognostic factor for allcause mortality among these patients [6,7]. Comorbidity may affect the timing of diagnosis by delaying health care-seeking or, conversely, increasing the frequency of health care contacts [7], which may also influence the choice or aggressiveness of cancer treatment [8,9]. Other studies suggest that patients in lower socioeconomic positions receive suboptimal treatment [3,10,11].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Information on physical morbidity was collected from diagnoses recorded in the Danish National Patient Registry, coded by the Danish version of the International Classification of Diseases (ICD-8 and ICD-10). Physical morbidity was classified according to the Charlson Co-morbidity Index (CCI) (Charlson et al, 1987) as used in a previous study (Tetsche et al, 2008). The CCI (ranging from 0 to 38 points) was used in the regression model as a continuous variable, i.e., the displayed OR indicates the change in estimates by a one-point increase in CCI score.…”
Section: Explanatory Variablesmentioning
confidence: 99%